Co‐syndiospecific Alternating Copolymerization of Functionalized Propylenes and Styrene by Rare‐Earth Catalysts - Wang, Haobing; Wu, Xia; Yang, Yang; Nishiura, Masayoshi; Hou, Zhaomin (Angewandte Chemie International Edition, 2020)
The precise control of monomer sequence and stereochemistry in copolymerization is of much interest and importance for the synthesis of functional polymers, but studies toward this goal have met with only limited success to date. Now, the co‐syndiospecific alternating copolymerization of methoxyphenyl‐ and N,N‐dimethylaminophenyl‐functionalized propylenes with styrene by half‐sandwich rare‐earth catalysts is reported. This reaction efficiently afforded the corresponding functionalized propylene‐alt‐styrene copolymers with a perfect alternating sequence and excellent co‐syndiotacticity (rrrr >99 %), thus constituting the first example of co‐stereospecific alternating copolymerization of polar and non‐polar olefins. A perfect zig‐zag: The co‐stereospecific alternating copolymerization of functionalized propylenes with styrene by half‐sandwich rare‐earth catalysts is presented. It afforded the corresponding functionalized propylene‐alt‐styrene copolymers with a perfect alternating sequence and excellent co‐syndiotacticity (rrrr >99 %).